2013
DOI: 10.4236/ti.2013.41004
|View full text |Cite
|
Sign up to set email alerts
|

Information Communication Technology (ICT) Utilization in Private Universities in Uganda: Exploring Strategies to Improve. A Case of Uganda Christian University

Abstract: The study was an extension of a similar study by [1] conducted among local government staff in Uganda and was extended among staff at Uganda Christian University. A total of 108 respondents out of the accessible 130 representing 83.0% response rate was realized after administering the study instruments over a period of two (2) weeks. Of the 108 respondents, 70.4% constituted staff in administration, 8.0% heads of sections and 21.6% academic staff. Data was analyzed using different statistical techniques which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
1
2
1
Order By: Relevance
“…Based on the findings, it is found that IT infrastructure is reflected very well by the items used to measure it and there is a strong relationship between IT infrastructure of EMESYS and user satisfaction. This finding is supported by previous studies by Dasuki (2018), , Nwone (2014) and Kyakulumbye et al (2013). This meant that the better the IT infrastructure, the more satisfied the users of EMESYS are.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Based on the findings, it is found that IT infrastructure is reflected very well by the items used to measure it and there is a strong relationship between IT infrastructure of EMESYS and user satisfaction. This finding is supported by previous studies by Dasuki (2018), , Nwone (2014) and Kyakulumbye et al (2013). This meant that the better the IT infrastructure, the more satisfied the users of EMESYS are.…”
Section: Discussionsupporting
confidence: 85%
“…According to Nwone (2014), there is a significant relationship between infrastructural issues and user satisfaction of the web portal. (Kyakulumbye, Olobo, & Kisenyi, 2013) also found that organizational support systems, IT infrastructure and users' perceptions had a strong relationship on IT utilization. However, Byrd & Turner (2000) in their study on measuring the flexibility of information technology infrastructure find IT infrastructure had no impact on user satisfaction.…”
Section: It Infrastructurementioning
confidence: 86%
“…The main purpose of this research was to investigate the Utilization of Information Communication Technology and associated factors among academic staffs in Bahirdar University, Northwest Ethiopia. This study revealed that the status of ICT utilization among academic staffs in Bahirdar Universitywas 56.7%.This result was greater than the findings done in Christian university Uganda which reported as 45% of academic staffs had good ICT utilization habit [8]. This may be due to ICT facility access difference between the two institutions.…”
Section: Discussioncontrasting
confidence: 66%
“…Omona (2012) pointed out the challenge of financial restraints among Ugandan universities which has led to mismanagement and brain drain (Omona, 2012). The relevance of strategic planning in educational institutions in Uganda has not been given the attention it deserves, yet there is evidence of the immense role it plays in the performance of educational institutions (Kyakulumbye, Olobo & Kisenyi, 2013).…”
Section: Introductionmentioning
confidence: 99%